A comprehensive review of remimazolam for sedation - Nazir Noor; Rhorer Legendre; Alexandra Cloutet; Ahish Chitneni; Giustino Varrassi; Alan D. Kaye (Health Psychology Research)
Benzodiazepines are one of the most commonly used medications in the field of anesthesia. They offer excellent anxiolytic and amnestic properties ideal for the perioperative period when patient anxiety is understandably heightened. Remimazolam has presented a favorable alternative to some of the common intravenous anesthetic agents used given its fast onset of action, high safety profile, and reasonably short duration of action.